Prevalence of multimorbidity in general practice: a cross-sectional study within the Swiss Sentinel Surveillance System (Sentinella) - Excoffier, Sophie (BMJ Open, 2018)
OBJECTIVES: To estimate the prevalence of multimorbidity using a list of 75 chronic conditions derived from the International Classification for Primary Care, Second edition and developed specifically to assess multimorbidity in primary care. Our aim was also to provide prevalence data for multimorbidity in primary care in a country in which general practitioners (GPs) do not play a gatekeeping role in the health system. SETTING: A representative sample of GPs within the Swiss Sentinel Surveillance Network. PARTICIPANTS: 118 GPs completed a paper-based questionnaire about 25 consecutive patients of all ages between September and November 2015. There were no patient exclusion criteria. Recorded data included date of birth, gender and the patients’ chronic conditions. PRIMARY AND SECONDARY OUTCOME MEASURES: We estimated the prevalence of multimorbidity, defined as ≥2, and ≥3 chronic conditions stratified by gender and age group, and adjusted for clustering by GPs. We also computed the prevalence of each chronic condition individually and grouped by system. RESULTS: Data from 2904 patients were included (mean age (SD)=56.5 (20.5) years; male=43.7%). Prevalence was 52.1% (95% CI 48.6% to 55.5%) for ≥2 and 35.0% (95% CI 31.6% to 38.5%) for ≥3 chronic conditions, with no significant gender differences. Prevalence of two or more chronic conditions was low (6.2%, 95% CI 2.8% to 13.0%) in those below 20 but affected more than 85% (85.8%, 95% CI 79.6% to 90.3%) of those above the age of 80. The most prevalent conditions were cardiovascular (42.7%, 95% CI 39.7% to 45.7%), psychological (28.5%, 95% CI 26.1% to 31.1%) and metabolic or endocrine disorders (24.1%, 95% CI 21.6% to 26.7%). Elevated blood pressure was the most prevalent cardiovascular condition and depression the most common psychological disorder. CONCLUSION: In a country in which GPs do not play a gatekeeping role within the health system, the prevalence of multimorbidity, as assessed using a list of chronic conditions specifically relevant to primary care, is high and increases with age.